Reading Strategies Used in Reading Academic Texts by Students of High and Intermediate Reading Proficiency Levels - Johan Setiawan; Nani Indrajani Tjitrakusuma (Institute of Research and Community Outreach - Petra Christian University, 2021)
In this study, the reading strategies used by students of high and intermediate reading proficiency levels were qualitatively examined. Reading strategies are important factors that affect someone's reading proficiency. In the development of education, reading strategies are continuously carried out to facilitate the learning process and sharpen students' reading skills. The purpose of this study is to discover the reading strategies used by the English Department students with high and intermediate reading proficiency levels in reading academic texts. This study uses reading strategies theory by Grabe (2009) combined with the interview questions by Mokhtari and Reichard (2002) to examine the reading strategies of ten participants consisting of five people with high reading proficiency level and five other people with intermediate reading proficiency level. This study showed that students of high reading proficiency levels tend to use more reading strategies than students with intermediate reading proficiency level. The biggest difference is in the use of text-structure awareness and inferencing strategies. It indicates that the mastery of text structure is directly related to reading effectiveness. Without text structure awareness, other reading strategies such as summarizing, inferencing, and elaborative interrogation will be seriously disrupted. Keywords: Reading Strategies, Academic Text, High Reading Proficiency Level, Intermediate Reading Proficiency Level